Structural health monitoring with piezoelectric wafer active sensors - Giurgiutiu, Victor (Elsevier/Academic Press, 2008)
Printbegrnsninger: Der kan printes kapitelvis.
Title from title screen.
Keywords: Structural analysis (Engineering); Automatic data collection systems.; Piezoelectric devices.; Piezoelectric transducers.; elektronické knihy; electronic books